BAHASA TUBUH PEREMPUAN DALAM IKLAN KOSMETIKA DI TELEVISI ( SEBUAH ANALISIS WACANA) - Witjaksana, Gunawan; Samudi, Samudi (Jurnal The Messenger, 2010)
In the era of liberalization that characterized the television media with comodification various impressions to attract viewers, in many ways carried on various kinds of impressions displayed. No exception impressions cosmetic ads which in practice is clearly a lot of exploiting women's body language to attract the audience that they ultimately want to use the products offered. Cosmetics with herbs ad exploits women's bodies are often ignored ethics, especially related to KPI P3SPS and cultural and religious views of society and the rights of adolescents and women. The impact is certainly there was a negative. For that research using discourse analysis techniques to examine the use of body language in women's cosmetics advertisements on television to be attractive for the study. The goal is clear to see how the exploitation of women's body language in advertisements on television cosmetics. Through discourse analysis method of recording by cosmetics ads on television, and then analyzed by discourse analysis, it can be concluded that, of cosmetics advertisements on television were likely to utilize and exploit the   perfect female body , in order to reach an audience sympathetic to using products that offered them. Unfortunately, the exploitation of women's body language in the cosmetics ads, less attention to ethical and religious views of the majority of Muslims in Indonesia, so the ad tend ignore the interests of general public and particularly children, adolescents, and women themselves.